2021
DOI: 10.15376/biores.16.2.3046-3058
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of variability in results of acoustic tomographs in pedunculate oak (Quercus robur L.)

Abstract: Tree acoustic tomography is a widely used device supported method for tree stability assessment. In this work, the results of the three most commonly used devices for acoustic tomography of standing trees (ARBOTOM®, ArborSonic®, and PiCUS®) were compared on selected individuals of sessile oak in Brno, Czech Republic. According to the statistical analysis, there was a significant difference between values measured by the PiCUS® acoustic tomograph and those measured by both the ARBOTOM and ArborSonic® acoustic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Nevertheless, stressed trees are more inclined to different negative abiotic and biotic factors [ 5 ], which can irreversibly compromise the host tree’s stability [ 6 ]. To prevent such events, the extent of decay and tree stability are often evaluated through nondestructive device-supported methods [ 7 , 8 ]. One of the most common wood-decaying fungi influencing trees’ structural stability is F. fomentarius [ 6 , 9 ] whose presence is widely spread in both forest and urban environments [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, stressed trees are more inclined to different negative abiotic and biotic factors [ 5 ], which can irreversibly compromise the host tree’s stability [ 6 ]. To prevent such events, the extent of decay and tree stability are often evaluated through nondestructive device-supported methods [ 7 , 8 ]. One of the most common wood-decaying fungi influencing trees’ structural stability is F. fomentarius [ 6 , 9 ] whose presence is widely spread in both forest and urban environments [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that broadband acoustic devices, such as the tomograph used in this study, are more suitable for estimating damage to the internal parts of wood than narrowband devices. However, other studies by Cristini et al (2021) report that there are no statistically significant differences between the speeds measured by different tomograph devices.…”
Section: Resultsmentioning
confidence: 82%
“…Studies conducted by Kloiber et al (2016) have Cristini et al (2021) also point out that for an analysis of living trees, it is necessary to take the tomogram results, such as natural imperfections in the wood, fiber deflection, knots, as well as the quality of the wood surface, including roughness and the presence of microcracks. The correct shape, type, frequency, and orientation of the acoustic sensors also play a significant role in obtaining accurate results.…”
Section: Resultsmentioning
confidence: 99%
“…There are several scientific reasons why thinning in oak plantations is necessary. Thinning helps to reduce the spread of fungal diseases and insect infestations in oak populations [3][4]. Removing infected or infested trees prevents the further spread of pathogens or pests to healthy trees, thereby protecting the overall health of the stand.…”
Section: öKologie-und Umweltschutztechnologienmentioning
confidence: 99%